Application of Interactive Quizzes to Increase Interest in Learning Mathematics - Azhari, Alya; Adhimah, Olivia Khufyatul; Huda, Syaiful (Proceeding International Conference on Lesson Study, 2023)
This research aims to overcome problems in the post-Covid 19 learning process, namely the low interest in learning mathematics among students. The application of interactive quizzes is expected to increase interest in learning mathematics. This type of research is PTK (Classroom Action Research). The subjects of this research were 36 grade 7 students at SMPN 3 Candi. The data collection technique in this research used a questionnaire. The research results showed that there was an increase in students' interest in learning mathematics as indicated by the increase in the number of students with high interest in learning and the decrease in the number of students with low interest in learning. In cycle I, there were no students with low interest in learning, there were 20 students with moderate interest in learning and 16 students with high interest in learning, while in cycle II there were no students with low interest in learning, there were 14 students with moderate interest in learning and 22 students with high interest in learning.